SELECTION OF WORKS OF ART FOR THE PROCESS OF DEVELOPING SPIRITUAL AND MORAL IDEALS IN STUDENTS ON THE EXAMPLE OF ENGLISH CLASSICAL LITERATURE (International scientific-electronic journal “Pioneering studies and theories”, 2026)
Artistic works possess significant potential for effectively influencing an individual’s intellectual, moral-spiritual, and emotional-aesthetic development. Therefore, literary works have been actively used in the education and upbringing of individuals for centuries. English classical literature undoubtedly occupies an important place in the development of universal culture and the socio-cultural progress of society. In the context of Uzbekistan, the growing interest in learning the English language, young people’s ability to communicate in this language, as well as the educational potential of English classical literature in developing intellectual, moral-spiritual, and emotionalaesthetic qualities, indicate the expediency of using it in the formation of students’ moral and ethical ideals. The article examines the organization of pedagogical activities aimed at developing students’ moral and ethical ideals, as well as the selection of examples of English classical literature that contribute to achieving effectiveness in this process.